PENGEMBANGAN PERMAINAN TIC TAC TOE UNTUK MENINGKATKAN KEMAMPUAN LITERASI SISWA KELAS 2 SD NEGERI 1 LEMBANG CINA KABUPATEN BANTAENG - Raunatul Jannah; Sayidiman Sayidiman; Hartoto Hartoto (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
This study aims to produce and determine the feasibility of Tic Tac Toe game to improve the literacy skills of grade 2 students in SD Negeri 1 Lembang Cina, Bantaeng Regency. This type of research is research and development (R&D) with a research design using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection techniques used were media expert validation sheets, teacher responsse questionnaires, and documentation techniques. The results of the media feasibility study as a whole according to the criteria of the product qualification rating scale, namely the media expert validation, obtained valid criteria. The results of teacher responsses obtained very valid criteria. The effectiveness of the Tic Tac Toe game media is very practical for use by teachers and students. Thus, the product produced in this study is suitable for use as an educational game medium by grade 2 elementary school teachers to strengthen the literacy of grade 2 elementary school students. With this study, further researchers can develop Tic Tac Toe games that are even more interesting for students.